Analisis Faktor Sosial-Ekonomi dalam Mendorong Anak Melakukan Tindak Pidana - Uut Rahayuningsih; Alya Khairunnisa; Putri Amanda Wulandari; Audrie Annasya Paramitha (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, but in digital business practices, they often face legal challenges in business contracts, whether with suppliers, distributors, or marketplace platforms. This article examines aspects of legal protection for MSMEs in digital business contracts and identifies inequalities that occur in business relationships with large companies. This study uses a normative-juridical research method by analyzing business contract regulations in Indonesia as well as comparative studies with legal systems in other countries. This study concludes that MSMEs need more proactive regulations in ensuring fairness in digital business contracts so as not to experience exploitation from more dominant parties.